The Effect of Audit Committee and Audit Quality on Earnings Management in Manufacturing Companies in Bei - Manu Diada Rizky; Nabiella Annisya Mas Putri; Imelda Mariawasi; Trinandari Prasetya Nugraha (Yayasan Adra Karima Hubbi, 2024)
This study aims to further explore the impact of audit quality and the presence of an audit committee on earnings management practices in manufacturing companies. Over the period of 2019 to 2022, this study focuses on analyzing the trading of manufacturing companies in the sub-sectors of basic and chemical industry, ceramics and porcelain glass, metals and the like, plastics and packaging, and pulp and paper listed on the Indonesia Stock Exchange. Quantitative methods were used by analyzing the annual financial reports of seven different companies, which resulted in 20 separate data sets. In the analysis, the study utilized various statistical tools, including descriptive tests, classical assumptions, multiple linear regression, and hypothesis testing all run through SPSS software. The results of this study indicate that audit committee has no effect on earnings management and audit quality has a significant effect on earnings management.